Experimental and Numerical Investigation of Hard Rock Breakage by Indenter Impact - Hongxiang Jiang; Zhiyuan Cai; Ouguo Wang; Deguang Meng (Shock and Vibration)
To investigate the effect of indenter shape, impact energy, and impact velocity on the rock breakage performance, a test device for rock fragmentation by indenter impact was developed to obtain the rock breakage volume, depth, and area under different impact conditions. By comparing the rock breakage volume, depth, area, and specific energy consumption, the results show that indenter shape has a greater influence on the rock breakage performance than that of the impact velocity with the same impact energy, and impact energy plays a decisive role in rock breakage performance with an identical indenter shape and impact velocity. For the lowest to highest specific energy consumption, the order of indenter shape is cusp-conical, warhead, hemispherical, spherical-arc, and flat-top under the same impact energy and velocity, but the cusp-conical indenter is damaged after several impacts. The rock breakage volume, depth, and area all increase with the increase in impact energy, but the effect of the impact velocity could be ignored under the same impact energy. In addition, the rock breakage features of the numerical simulation and experiments are similar, which show that the crushing zone close to the indenter impact point is mainly caused by the high compressive stress, and then radial cracks are caused by the accumulative energy release. The findings of this study will contribute to progress in the performance and efficiency for percussive rock drilling.